Carnosic acid ameliorates depressive‐like symptoms along with the modulation of FGF9 in the hippocampus of middle carotid artery occlusion‐induced Sprague Dawley rats. (11th August 2020) - Azhar, Mudassar; Zeng, Guirong; Ahmed, Ayaz; Dar Farooq, Ahsana; Choudhary, Muhammad I.; De‐Jiang, Jiang; Liu, Xinmin
Abstract : The increased survival rate of stroke patients has led to the higher incidences of post‐stroke depression. Carnosic acid has the ability to cross blood brain barrier with good neuro‐modulatory actions. Recently, inclined level of fibroblast growth factor 9 (FGF9) in the postmortem brain of the depressed patients was noted. Therefore, in the present study, the effect of carnosic acid on post‐stroke depression‐like behavior, and the expression of FGF9 were evaluated. After 3 weeks of middle carotid artery occlusion in Sprague Dawley rats, carnosic acid (20 and 40 mg/kg) was administered for 2 weeks. Sucrose preference test, forced swimming test, and open field test were performed and hippocampi were analyzed for FGF9 and FGFR‐3. In comparison to post‐stroke depressed rats, carnosic acid increased the sucrose preference, and reduced the immobility time of the rats by ~2×. The speed and distance‐covered were also increased. At 40 mg/kg, FGF9 was reduced by ~3× while FGFR‐3/Actin was increased by ~1.5×. Altogether results suggest anti‐depressant‐like activity of carnosic acid in post‐stroke depressed rats with decreased expression of hippocampal FGF9.